Effect of cryopreservation and semen extender on extracellular vesicles isolated from bull semen - Capra, Emanuele; Frigerio, Roberto; Lazzari, Barbara; Turri, Federica; Gaspari, Giulia; Pascucci, Luisa; Stella, Alessandra; Lange Consiglio, Anna; Pizzi, Flavia; Cretich, Marina (Frontiers in Veterinary Science, 2024)
Introduction: Semen cryopreservation is the most popular practice for semen production for artificial insemination and in vitro fertilization in cattle. The Seminal plasma contains extracellular vesicles (spEVs) which modulate sperm viability and function during oocyte fecundation. The study of spEVs in frozen-thawed semen doses may yield novel indicators for predicting bull fertility, but the presence of the semen extender may hinder molecular profiling of spEVs. The aim of this study was to provide extensive characterization of EVs isolated from seminal plasma before and after the cryopreservation process and the addition of a commercial animal protein-free semen extender to understand the potential influence of EVs originating from the extender in hindering the use of spEVs derived biomarkers for assessment of bull fertility. Methods: EVs were isolated from the seminal plasma (with or without the extender), from the cryopreserved straw devoid of spermatozoa, and from the extender using two different methods, ultracentrifugation (UC) and size exclusion chromatography (SEC), and characterized for their structure and composition. Results: Physical characterization of EVs showed that size and particle numbers were related to the method of isolation. spEVs were larger but less abundant (UC:168.9 nm, n=2.68 × 10 9 ; SEC:197.0 nm, n=6.42 × 10 9 ) compared to extender EVs (UC:129.0 nm, n=2.68 × 10 11 ; SEC:161.8 nm, n=6.47 × 10 11 ). Western blotting analysis (WB) confirmed the presence of typical EV markers in spEVS: the membrane bound CD9 (25kDa) and the luminal markers Alix (96kDa) and TSG101(48KDa). Although Transmission Electron Microscopy confirmed the presence of a lipid bilayer structure in all preparations, no specific EV markers were detected in the vesicles isolated from extender when the Single Molecule Array (SiMoa) was used. A total of 724 Bos taurus miRNAs were identified in at least one preparation. The percentage of miRNAs identified in EVs from the extender (0.05-0.49% of the total reads) was lower than in the preparation containing spEVs (10.56-63.69 of the total reads). Edge-R identified a total of 111 DE-miRNAs between EVs isolated from the extender by two methods.